2012
DOI: 10.1073/pnas.1219885110
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis identifies a locus for plasma von Willebrand factor undetected by genome-wide association

Abstract: The plasma glycoprotein von Willebrand factor (VWF) exhibits fivefold antigen level variation across the normal human population determined by both genetic and environmental factors. Low levels of VWF are associated with bleeding and elevated levels with increased risk for thrombosis, myocardial infarction, and stroke. To identify additional genetic determinants of VWF antigen levels and to minimize the impact of age and illness-related environmental factors, we performed genome-wide association analysis in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
121
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 48 publications
7
121
1
Order By: Relevance
“…Indeed, carriers of the B antigen have higher VWF levels compared with carriers of the A antigen and carriers of both antigens have the highest VWF levels. 33, 34 The second locus is within the VWF gene. It has been well established that common genetic polymorphisms in the VWF gene contribute to the variability in VWF:Ag levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, carriers of the B antigen have higher VWF levels compared with carriers of the A antigen and carriers of both antigens have the highest VWF levels. 33, 34 The second locus is within the VWF gene. It has been well established that common genetic polymorphisms in the VWF gene contribute to the variability in VWF:Ag levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 The VWF level we observed in C57BL/ 6J mice (3.4 mg/mL, Figure 2A) is ;1/3 of the average VWF level in healthy humans, consistent with a previous report. 40 Whereas VWF levels in healthy humans range ;3-fold (from ;5 to ;15 mg/mL), 41 VWF levels among inbred mouse strains vary even more widely (.10-fold). 30 This latter variation is due to differences in VWF synthesis/secretion and clearance among mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…The encode of VWF is located on short arm of chromosome 12 and the 52 exons of the gene in humans [9,26] . The single-gene associations between plasma vWF: Ag concentrations and variants at the angiotensin-coverting enzyme, the FUR2 locus, lipoproteinreceptor-related protein, and arginine vasopressin 2 receptor have been reported in previous studies in humans [16] . Kramer et al [3] investigated German Shorthaired Pointers having type II vWD and they found statistical importance between vWF variant nucleotide in exon 28 and vWF multimer deficiencies.…”
Section: Discussionmentioning
confidence: 58%
“…Von Willebrand's disease is an acquired or inherited bleeding disorder common in humans and dogs [3] . In human beings estimated prevalence of vWD has been reported between 0.01-0.02% [9,16] . Castaman et al [17] point out that with a prevalence of 1% in general population; the ratio of visible clinical symptoms is only 0.01%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation